Nonverbal behavioural characteristics of children and adolescents with type 1 diabetes mellitus and emotional disorders - Yana Vladimirovna Girsh; O A Gil'burd; N A Mironova (Сахарный диабет)
Aim. To estimate clinical significance of nonverbal behaviour analysis and ethological method in diagnostics of emotional disorders in children and adolescents with type 1 diabetes mellitus (T1DM). Material and Methods. 87 patients with T1DM aged 12.34?4.6 years were enrolled in this study. Ethological analysis was based on Glossary of Human Nonverbal Behaviour; behavioural characteristics were formalized according to Human Ethological Signs Scale (HESS). Results. Nonverbal signs of anxiety in children with long experience of T1DM were more diverse and prominent. Average occurrence of complete ethological repertoire was 80.6% and 76.4%, respectively. Children with clinical history of T1DM greater than 3 years demonstrated complete repertoire in 86.6% of cases, with that of only 76.4% of more recently diagnosed. Conclusion. Ethological analysis of nonverbal behaviour in children and adolescents with T1DM improves informative value of clinical examination and complements verification of psychopathological data on emotional disorders in this category of patients.